Treatment-resistant, five-year long, postpartum-onset Capgras episode resolving after electroconvulsive therapy. (April 2015) - Rapinesi, Chiara; Kotzalidis, Georgios D; Casale, Antonio Del; Ferri, Vittoria Rachele; Di Pietro, Simone; Scatena, Paola; Serata, Daniele; Danese, Emanuela; Sani, Gabriele; Koukopoulos, Alexia E; Angeletti, Gloria; Girardi, Paolo
Postpartum psychosis, which rarely presents with Capgras syndrome (delusional misidentification), requires rapid symptom resolution. First-line drugs have important drawbacks, such as delayed onset of clinical response and secretion in breast milk. In this report, we report successful treatment of a treatment-resistant woman presenting with treatment-resistant Capgras syndrome, with onset during postpartum. A 36-year-old woman had presented with Capgras syndrome during postpartum. For more than five years, she believed her son and other family members were substituted by impostors. All adequately administrated treatments were unsuccessful. We suggested electroconvulsive therapy to overcome treatment resistance. After six electroconvulsive therapy sessions, delusions of doubles subsided and other symptoms improved. She was discharged two weeks later with a mood stabilizer and low-dose atypical antipychotic combination and is well at the one-and-a-half-year follow-up. Electroconvulsive therapy followed by a mood stabilizer–antipsychotic drug combination showed rapid, permanent, and effective control of long-standing Capgras syndrome in a young woman.